Factors affecting the completion of merger and acquisition deals of foreign companies in Vietnamese market - Le, Ngoc Thanh (H. : ĐHQGHN, 2020)
The purpose of this project is to examine the factors affecting the completion of merger and acquisition (M&A) deals of multinational companies in the Vietnamese market. Ĩ proposed five factors that can have an impact on the execution of the deals. These factors include cultural distance, deal size, economic growth, investing experience and industry match. In this project, a sample of 442 deals which were the M&A deals in Vietnam between 2000 and 2018, combine both completed - deals and abandoned - deals. Using logistic regression model, the empirical analysis indicates that when the deal is likely to be completed when (1) the cultural distance between acquirer and target firm is low, (2) the deal value is small, (3) acquirer has more experience in investing in the Vietnamese market and (4) acquirer has the same or close industry with the target firm.